2013
DOI: 10.1093/europace/eut127
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of cardioverter defibrillators with minimal fluoroscopy using a three-dimensional navigation system: a feasibility study

Abstract: Fluoroscopy-free defibrillators implantation is feasible using a navigation system. Suitable placement of the proximal coil is a critical stage and requires a reliable and complete reconstruction of the superior vena cava.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…To our knowledge, prior reports have described the feasibility of cardiac device implantation utilizing a minimal radiation exposure technique, which combining 3D mapping systems and fluoroscopy . Seldom single cases have described the feasibility of pacemaker implantation without fluoroscopy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, prior reports have described the feasibility of cardiac device implantation utilizing a minimal radiation exposure technique, which combining 3D mapping systems and fluoroscopy . Seldom single cases have described the feasibility of pacemaker implantation without fluoroscopy .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, prior reports have described the feasibility of cardiac device implantation utilizing a minimal radiation exposure technique, which combining 3D mapping systems and fluoroscopy. [11][12][13][14] Seldom single cases have described the feasibility of pacemaker implantation without fluoroscopy. [5][6][7][8][9]15 In our study, all permanent pacemakers were successfully implanted with satisfactory parameters and without any complications using the Ensite NavX system.…”
Section: Discussionmentioning
confidence: 99%
“…They did not use fluoroscopy to confirm that the active fixation screw was deployed and they noted one lead dislodgement requiring reoperation. Castrejon‐Castrejon et al described the implantation of mostly single‐chamber ICD leads in 35 adult patients using minimal fluoroscopy . Del Greco et al reported four patients in whom biventricular defibrillators were implanted with the aid of Ensite in addition to fluoroscopy, although they still required a range of 4.2–16.9 minutes of fluoroscopy …”
Section: Discussionmentioning
confidence: 99%
“…Castrejon-Castrejon et al described the implantation of mostly singlechamber ICD leads in 35 adult patients using minimal fluoroscopy. 20 Del Greco et al reported four patients in whom biventricular defibrillators were implanted with the aid of Ensite in addition to fluoroscopy, although they still required a range of 4.2-16.9 minutes of fluoroscopy. 8 This report describes our experience of using 3D mapping in pediatric patients undergoing implantation of transvenous PMs or defibrillators.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, such EAMs are not routinely used during pacemaker implantation. However, some experiences with pacemakers and defibrillators in adults have been reported, in a grown‐up congenital heart defect (CHD) patient and in pediatric patients . In children with complete atrioventricular block (CAVB), the endocardial pacing site is often the right ventricular (RV) apex (RVA), although alternative RV sites (RVAPS) have been proposed to prevent or reduce RV pacing‐induced left ventricular (LV) dysfunction .…”
Section: Introductionmentioning
confidence: 99%